In Vitro Validation of Regional Circumferential Strain Assessment in a Phantom Aortic Model Using Cine Displacement Encoding With Stimulated Echoes MRI. Issue 6 (27th October 2021) - Wilson, John S.; Islam, Muhammad; Oshinski, John N.
Abstract : Background: A novel application of cine Displacement ENcoding with Stimulated Echoes Magnetic Resonance Imaging (DENSE MRI) has recently been described to assess regional heterogeneities in circumferential strain around the aortic wall in vivo; however, validation is first required for successful clinical translation. Purpose: To validate the quantification of regional circumferential strain around the wall of an aortic phantom using DENSE MRI. Study Type: In vitro phantom study. Population: Three polyvinyl alcohol aortic phantoms with eight axially oriented nitinol wires embedded evenly around the walls. Field Strength/Sequence: 3 T; gradient‐echo aortic DENSE MRI with spiral cine readout, gradient‐echo phase‐contrast MRI (PCMR) with Cartesian cine readout. Assessment: Phantoms were connected to a pulsatile flow loop and peak DENSE‐derived regional circumferential Green strains at 16 equally spaced sectors around the wall were assessed according to previously published algorithms. "True" regional circumferential strains were calculated by manually tracking displacements of the nitinol wires by two independent observers. Normalized circumferential strains (NCS) were calculated by dividing regional strains by the mean strain. Finally, DENSE‐derived regional strain was corrected by multiplying regional DENSE NCS by the mean strain calculated from the diameter change on the PCMR. Statistical Tests: One‐sample t ‐test, Paired‐sample t ‐test, and analysis of variance with Bonferroni correction, coefficient of variation (CoV), Bland–Altman analysis; P  < 0.05 was considered statistically significant. Results: Aortic DENSE MRI significantly overestimated circumferential strain compared to the wire‐tracking method (mean difference and SD 0.030 ± 0.014, CoV 0.31). However, NCS demonstrated good agreement between DENSE and wire‐tracking data (mean difference 0.000 ± 0.172, CoV 0.15). After correcting the DENSE‐derived regional strain, the mean difference in regional circumferential strain between DENSE and wire‐tracking was significantly reduced to 0.006 ± 0.008, and the CoV was reduced to 0.18. Data Conclusion: For aortic phantoms with mild spatial heterogeneity in circumferential strain, the previously published aortic DENSE MRI technique successfully assessed the regional NCS distribution but overestimated the mean strain. This overestimation is correctable by computing a more accurate mean circumferential strain using a separate cine scan. Level of Evidence: 2 Technical Efficacy: Stage 2